Health and Beauty : A Book for Girls - Foley, Elizabeth; Cocker, Edith A. (London : The Health & Cleanliness Council)
1939-10 1939 1930s 27 pages ; illustrations that can eat into the enamel whilst you sleep. In a neglected mouth decay spreads rapidly and will result in a row of discoloured ugly teeth. Brush them up and down and from side to side inside as well as outside, and keep your toothbrush clean and strictly to yourself. The toothbrush should be put where it can dry. It should be renewed every few months. Raw apples and other fruits help to cleanse the teeth, and you can diet your teeth by taking plenty of milk, butter, eggs, cheese and fresh vegetables, including crisp salads, and fruits. SPARKLING EYES You must be very careful not to abuse your eyes. It is so easy for even the prettiest eyes to become blood-shot and red-rimmed. Reading or sewing in a bad light will do this; straining to read or sew at dusk is a very bad habit and may cause permanent damage to your sight. [illustration] Never go to an unqualified person. Try to manage always to have an electric light of sufficient candle-power for the particular work you have to do. Switch on your light immediately the sun has sunk, and never allow yourself to peer until the last vestige of daylight has gone. Move your desk in the office and your chair at home so that the light shines over your left shoulder on to your book, paper or needlework, and not into your eyes. A frosted or opal bulb gives a kind and not too glaring light. Arrange the light in your bedroom also so that it is reflected from your mirror on to [illustration] 11 177/5/8/4